The analysis of the information on algae and revised checklist from Danube Delta Biosphere Reserve - TÖRÖK Liliana (Scientific Annals of the Danube Delta Institute, 2009)
The present paper contains an analysis of the available information dealing with the diversity of algae from Danube Delta Biosphere Reserve. Undesirable mistake: wrong nominalization of the scientific names which have been found in reference sources or synonyms of the species have been crowed out from the revised checklist.